1994
DOI: 10.1056/nejm199406233302506
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Four Computer-Based Diagnostic Systems

Abstract: The results provide a profile of the strengths and limitations of these computer programs. The programs should be used by physicians who can identify and use the relevant information and ignore the irrelevant information that can be produced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
163
0
4

Year Published

1995
1995
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 270 publications
(171 citation statements)
references
References 33 publications
4
163
0
4
Order By: Relevance
“…Adult critical care Diagnostic DXplain [28] Mortality and length of stay prediction [9,29] Alert and reminder Ventilator induced lung injury [84] Blood pressure variability while on vasopressors [32] Adverse drug reactions [19] Drug induced thrombocytopenia [30] Epidural hematoma with neuraxial anesthesia [31] Protocol/procedure Acute respiratory distress syndrome [33][34][35] Sepsis [21] VTE prophylaxis and events in trauma patients [37] VTE prophylaxis [38,39] Tidal volume during mechanical ventilation [36] Management…”
Section: Type Of Support Tool Example or Subjectmentioning
confidence: 99%
See 1 more Smart Citation
“…Adult critical care Diagnostic DXplain [28] Mortality and length of stay prediction [9,29] Alert and reminder Ventilator induced lung injury [84] Blood pressure variability while on vasopressors [32] Adverse drug reactions [19] Drug induced thrombocytopenia [30] Epidural hematoma with neuraxial anesthesia [31] Protocol/procedure Acute respiratory distress syndrome [33][34][35] Sepsis [21] VTE prophylaxis and events in trauma patients [37] VTE prophylaxis [38,39] Tidal volume during mechanical ventilation [36] Management…”
Section: Type Of Support Tool Example or Subjectmentioning
confidence: 99%
“…Examples of CDS systems in adult critical care are provided in Table 1. Diagnostic support tools are available to assist in disease identification and also for using symptoms and patient condition on admission to predict outcome [9,28,29] . Ranson's criteria and various APACHE models are examples that have been validated using real time data to predict mortality risk in critically ill patients [29] .…”
Section: Type Of Support Tool Example or Subjectmentioning
confidence: 99%
“…A wide variety of techniques has been used to do this, predominantly stemming from Bayesian probability, decision analysis, and artificial intelligence. After evaluations showed a poor uptake of expert systems (Miller & Masarie, 1990) and modest benefit of diagnostic systems (Berner et al, 1994), emphasis has shifted towards the implementation of clinical practice guidelines and protocols. These systems generally build on computer-interpretable models of the guidelines or protocols in question, and are described in Section 4.2.…”
Section: Computerized Decision Supportmentioning
confidence: 99%
“…9 In that study, four DDX generators were evaluated, two of which are no longer on the market, and only one of which met the inclusion criteria of the current study. Berner and colleagues concluded that on average the tools had a relatively mediocre sensitivity of approximately 50-70% for the correct diagnosis, and a companion editorial by Kassirer gave the tools a grade of C. 10 The current study by Bond and colleagues has many strengths.…”
mentioning
confidence: 99%